Mixed primary prostatic carcinoma with acinar, neuroendocrine and ductal components - Alfredo E. Romero-Rojas (Archivio Italiano di Urologia e Andrologia, 2014)
Mixed tumors in the prostate gland have been described; they are primarily originate in the gland or are the product of metastatic compromise. Mixed primary epithelial carcinomas of the prostate are very rare; here we report the case of a 72-years-old man with histopathologic findings of a primary prostate mixed carcinoma, showing characteristics of acinar, ductal and neuroendocrine adenocarcinoma. We also discuss the clinical, diagnostic, and therapeutic aspects of these uncommon mixed neoplasms.